2020
DOI: 10.1111/ene.14339
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms and quality of life in Spanish patients with Alzheimer’s disease during the COVID‐19 lockdown

Abstract: Background and purposeThe COVID epidemic is affecting individuals worldwide, and Alzheimer's disease (AD) and amnesic mild cognitive impairment (MCI) patients are at risk due to their characteristics and age.We analysed the impact of the pandemic on these patients' neuropsychiatric symptoms and their quality of life after five weeks of lockdown in Spain. MethodsWe tested 40 subjects with a diagnosis of MCI (20) or mild AD (20) from the Cognitive Stimulation Program of Cognitive Disorders Unit. All patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
188
2
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(214 citation statements)
references
References 11 publications
12
188
2
12
Order By: Relevance
“…Accordingly, Canevelli and colleagues ( 15 ) reported an increase of depressed mood within the first month of lockdown in an Italian sample of subjects with dementia. On the other hand, in a similar cohort in Spain, no worsening of depression was observed after 5 weeks of home confinement ( 9 ). Additionally, increased hopelessness was reported in subjects with AD after interruption of experimental trials on potential disease-modifying drugs.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Accordingly, Canevelli and colleagues ( 15 ) reported an increase of depressed mood within the first month of lockdown in an Italian sample of subjects with dementia. On the other hand, in a similar cohort in Spain, no worsening of depression was observed after 5 weeks of home confinement ( 9 ). Additionally, increased hopelessness was reported in subjects with AD after interruption of experimental trials on potential disease-modifying drugs.…”
Section: Resultsmentioning
confidence: 96%
“…Accordingly, Canevelli and colleagues ( 15 ) reported that apathy presented in more than 25% of quarantined subjects with dementia within the first month of lockdown in Italy. Apathy also overwhelmingly increased over time, as compared with depressed mood, in subjects with dementia and home confinement ( 9 ). Patients with apathy are less likely to initiate behaviors necessary to impede the transmission of the virus, including selfcare and personal hygiene, washing hands, or covering their mouth while coughing ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Spanish study [57], 40 subjects diagnosed with MCI (20) or mild AD (20) who had performed neuropsychological and clinical assessment during the month prior to the lockdown, were reevaluated after 5 weeks of social isolation via the neuropsychiatric scale (NPI) and EuroQol-5D. The total basal NPI score worsened by about 6 points, from 33.75 to 39.05 after con nement, with the appearance of various neuropsychiatric symptoms including apathy and anxiety in subjects with MCI and apathy, agitation and aberrant motor behavior in AD patients.…”
Section: Impact Of Covid-19 On Psychiatric Health Of Patients With Comentioning
confidence: 96%